58.1k views
3 votes
S= 2bh+2bw+2hw solve for w

1 Answer

2 votes


Solution, solve\:for\:w,\:s=2bh+2bw+2hw\quad :\quad w=(s-2bh)/(2\left(b+h\right));\quad \:2\left(b+h\right)\\e \:0


Steps:


s=2bh+2bw+2hw


\mathrm{Switch\:sides},\\2bh+2bw+2hw=s


\mathrm{Subtract\:}2bh\mathrm{\:from\:both\:sides},\\2bh+2bw+2hw-2bh=s-2bh


Simplify,\\2bw+2hw=s-2bh


\mathrm{Factor}\:2bw+2hw,\\\mathrm{Rewrite\:as},\\2bw+2hw,\\\mathrm{Factor\:out\:common\:term\:}2w,\\2w\left(b+h\right),\\2w\left(b+h\right)=s-2bh


\mathrm{Divide\:both\:sides\:by\:}2\left(b+h\right);\quad \:2\left(b+h\right)\\e \:0,\\(2w\left(b+h\right))/(2\left(b+h\right))=(s)/(2\left(b+h\right))-(2bh)/(2\left(b+h\right));\quad \:2\left(b+h\right)\\e \:0


\mathrm{Simplify},\\w=(s-2bh)/(2\left(b+h\right));\quad \:2\left(b+h\right)\\e \:0


\mathrm{The\:Correct\:Answer\:is\:w=(s-2bh)/(2\left(b+h\right));\quad \:2\left(b+h\right)\\e \:0}


\mathrm{Hope\:This\:Helps!!!}


\mathrm{-Austint1414}

User U Avalos
by
5.8k points